2019
DOI: 10.1002/alr.22428
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and harms of aspirin desensitization for aspirin‐exacerbated respiratory disease: a systematic review and meta‐analysis

Abstract: Background: Aspirin desensitization is increasingly recommended for the treatment of aspirin-exacerbated respiratory disease (AERD). The objective of this study is to systematically review the efficacy and safety of aspirin desensitization in patients with AERD. Methods:We searched MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials, and World Health Organization (WHO) International Clinical Trials Registry Platform from inception to January 5, 2019. We included randomized trials and comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 60 publications
1
40
0
1
Order By: Relevance
“…Other work has identified that within 5 years of their initial surgery, over 35% of AERD patients will require a second surgical intervention 23 . Aspirin desensitization and daily aspirin maintenance therapy has been shown to improve symptoms, endoscopy, and quality of life, and revision FESS rates as low as 9% have been reported 23‐26 . Current expert panel guidelines state that aspirin desensitization with daily aspirin maintenance therapy is indicated for recurrent polyps after surgery, severe asthma, and sinus symptoms despite standard therapy, or a need for aspirin therapy due to cardiac disease or stroke 27 .…”
Section: Aerdmentioning
confidence: 99%
See 1 more Smart Citation
“…Other work has identified that within 5 years of their initial surgery, over 35% of AERD patients will require a second surgical intervention 23 . Aspirin desensitization and daily aspirin maintenance therapy has been shown to improve symptoms, endoscopy, and quality of life, and revision FESS rates as low as 9% have been reported 23‐26 . Current expert panel guidelines state that aspirin desensitization with daily aspirin maintenance therapy is indicated for recurrent polyps after surgery, severe asthma, and sinus symptoms despite standard therapy, or a need for aspirin therapy due to cardiac disease or stroke 27 .…”
Section: Aerdmentioning
confidence: 99%
“…Likely there is a lack of accessibility and/or adoption of this treatment in some practices, 28 or patients and physicians decide against maintenance therapy due to risks of gastrointestinal complications or challenges with convenience of this daily treatment. Additionally, most studies regarding aspirin maintenance have had relatively short follow‐up and some patients do not respond to aspirin desensitization 24,29 …”
Section: Aerdmentioning
confidence: 99%
“…To manage this challenging disease, aspirin desensitization (AD) has emerged as an adjunctive therapy. AD was shown to improve sinonasal symptoms, quality of life, and reduce the recurrence of nasal polyps after surgery 4‐7 . Although AD provides meaningful clinical improvement, the benefits are counterbalanced by relatively high rates of adverse effects and subsequent discontinuation of therapy 7 .…”
mentioning
confidence: 99%
“…AD was shown to improve sinonasal symptoms, quality of life, and reduce the recurrence of nasal polyps after surgery 4‐7 . Although AD provides meaningful clinical improvement, the benefits are counterbalanced by relatively high rates of adverse effects and subsequent discontinuation of therapy 7 . In addition, AD may not be an easily accessible treatment, with one recent study demonstrating that only 7% of AERD patients in the United States underwent AD 8 .…”
mentioning
confidence: 99%
“…The diagnosis of nasal polyps was also usually made after the diagnosis of asthma. Chu et al., in a review article, evaluate the benefits and risks of aspirin desensitization. Their meta‐analysis provides high‐certainty and moderate‐certainty evidence that, compared to placebo, aspirin desensitization in the AERD meaningfully improves upper respiratory symptoms and disease‐related quality of life (QOL).…”
mentioning
confidence: 99%